Neuronal epigenetics and the aging synapse - Azpurua, Jorge; Eaton, Benjamin A. (Frontiers in Cellular Neuroscience, 2015)
Two of the most salient phenotypes of aging are cognitive decline and loss of motor function, both of which are controlled by the nervous system. Cognition and muscle contraction require that neuronal synapses develop and maintain proper structure and function. We review the literature on how normal physiological aging disrupts central and peripheral synapse function including the degradation of structure and/or control of neurotransmission. Here we also attempt to connect the work done on the epigenetics of aging to the growing literature of how epigenetic mechanisms control synapse structure and function. Lastly, we address possible roles of epigenetic mechanisms to explain why the basal rates of age-related dysfunction vary so widely across individuals.